Clinical MR imaging in Parkinson's disease: How useful is the swallow tail sign?. Issue 7 (24th May 2021) - Prasuhn, Jannik; Neumann, Alexander; Strautz, Robert; Dreischmeier, Shalida; Lemmer, Felicitas; Hanssen, Henrike; Heldmann, Marcus; Schramm, Peter; Brüggemann, Norbert
Abstract: Background: With conventional MRI, no Parkinson's disease (PD)‐specific abnormalities can be detected. However, there is a critical need for accompanying neuroimaging markers to guide the diagnosis. With high‐resolution susceptibility‐weighted MRI (SWI) sequences, the imaging of nigrosome‐1 (N1) is possible. The so‐called swallow tail sign (STS) has been proposed as a suitable neuroimaging marker for the diagnosis of PD. Objectives: To investigate whether the absence of the STS can be applied for distinguishing PD patients from healthy controls (HCs). Methods: SWI images of 44 PD patients and 50 age‐ and gender‐matched HCs were investigated using a 3T MRI scanner. Two trained neuroradiologists blind‐rated the images and evaluated whether the STS was absent (1) on one side or (2) both sides of the participant's midbrain. Results: Our results confirmed good interrater reliability comparable to previously published studies. However, we did not identify any group differences between PD patients and HCs. Measures of diagnostic values revealed overall poor diagnostic performance. Conclusions: Even though previously stated, our study does not confirm the potential use of the STS as a supportive neuroimaging marker for PD in a clinical setting. In conclusion, there is a critical need for improvements in N1‐targeted MRI sequences and the development of advanced segmentation algorithms. Abstract : Examples for a healthy‐appearing swallow tail sign in a diseased individual (A) and an absent swallow tail sign in a healthy individual (B).